The effects of project-based learning on high school students' speaking skill in Tra Vinh province - Dương Thúy Thanh (Trường Đại học Trà Vinh, 2021)
In accordance with the research problems above, the study attempts to find out whether PBL has any influence on high school students’ speaking ability or not and what the responses of students’ attitudes will be towards speaking skill by using PBL.